Paroxysmal Tachycardia Diagnosed by ECG247 Smart Heart Sensor in a Previously Healthy Child - Jarle Jortveit; Andreas Früh; Hans Henrik Odland (Case Reports in Pediatrics)
Supraventricular tachycardia (SVT) is the most common symptomatic heart rhythm disorder in children and adolescents. ECG recordings of the heart rhythm during episodes is necessary for the diagnosis and for the selection of treatment. However, conventional long-term ECG recording systems may miss the diagnosis due to the disease’s intermittent nature. Novel adhesive patch ECG monitors, like ECG247 Smart Heart Sensor, may represent new important diagnostic tools in children and adolescents with symptoms of heart rhythm disorders. We report a case of tachyarrhythmia in a previously healthy 12-year-old child.